MODERN IDEAS IN THE THEORY OF HEART FUNCTION AND STRUCTURE (REVIEW OF LITERATURE) (Western European Journal of Medicine and Medical Science, 2024)
The article reveals the processes and mechanisms of the diastolic function of the pericardium - the heart sac. It was found that the pericardium is not only a sac that surrounds the heart, but also ensures the stabilization of the diaphragmatic dome during systole of the heart chambers and ventricles, during breathing processes, and determines the constancy of the heart volume. The relationship between the heart's activity and the "legs of the diaphragm" muscles, which connect the ligament centers of the diaphragm with the vertebral column and are located in the abdominal cavity under the diaphragm, is revealed. It was found that the "legs of the diaphragm" muscles control the height of the ligament centers of the diaphragm. During diastole of the heart ventricles, these powerful muscles contract, pulling the diaphragmatic center downward, ensuring more efficient and faster filling of the heart ventricles with blood, increasing the vacuum in the pericardial cavity. A strong connection is formed between the heart and the vertebral column: myocardium↔epicardium↔pericardial cavity↔pericardium↔tendinous center↔diaphragmatic pedicle↔vertebral column (lumbar vertebrae L3-5).